2014
DOI: 10.1177/0001839214563975
|View full text |Cite
|
Sign up to set email alerts
|

Creativity from Constraint? How the Political Correctness Norm Influences Creativity in Mixed-sex Work Groups

Abstract: As work organizations become increasingly gender diverse, existing theoretical models have failed to explain why such diversity can have a negative impact on idea generation. Using evidence from two group experiments, this paper tests theory on the effects of imposing a political correctness (PC) norm, one that sets clear expectations for how men and women should interact, on reducing interaction uncertainty and boosting creativity in mixed-sex groups. Our research shows that men and women both experience unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 78 publications
10
95
2
Order By: Relevance
“…Over 30 years of research on the group diversity to performance relationship has demonstrated that the value in diversity tends to emerge only under the right conditions. Simply convening heterogeneous individuals together is insufficient for synergistic outcomes to emerge; without clear motivations, norms, and accountability structures to encourage group members to challenge each other's perspectives and persevere in their debate of multiple possible solutions, the different perspectives that may be held by diverse group members are often not shared or used or when expressed, often lead to disruptive conflict (Chatman, 2010;Crandall, Eshleman, & O'Brien, 2002;Goncalo, Chatman, Duguid, & Kennedy, 2015;Hobman, Bordia, & Gallois, 2004;Mitchell, Nicholas, & Boyle, 2009). The focus of synergy climate is thus on employees' shared perceptions about what is expected and rewarded with regard to how employees interact in order to learn from and leverage their synergistic potential.…”
Section: Fairness and Discrimination Versus Synergymentioning
confidence: 99%
“…Over 30 years of research on the group diversity to performance relationship has demonstrated that the value in diversity tends to emerge only under the right conditions. Simply convening heterogeneous individuals together is insufficient for synergistic outcomes to emerge; without clear motivations, norms, and accountability structures to encourage group members to challenge each other's perspectives and persevere in their debate of multiple possible solutions, the different perspectives that may be held by diverse group members are often not shared or used or when expressed, often lead to disruptive conflict (Chatman, 2010;Crandall, Eshleman, & O'Brien, 2002;Goncalo, Chatman, Duguid, & Kennedy, 2015;Hobman, Bordia, & Gallois, 2004;Mitchell, Nicholas, & Boyle, 2009). The focus of synergy climate is thus on employees' shared perceptions about what is expected and rewarded with regard to how employees interact in order to learn from and leverage their synergistic potential.…”
Section: Fairness and Discrimination Versus Synergymentioning
confidence: 99%
“…In negotiation, women often behave differently than men only when there is ambiguity about what behavior is appropriate (Bowles et al, 2005;Kennedy et al, 2015;Kray & Gelfand, 2009;Mazei et al, 2015;Miles & LaSalle, 2009). Mixed-gender interactions could be more uncertain than same-gender interactions (Goncalo, Chatman, Duguid, & Kennedy, 2014). Consequently, it could be that within mixed-sex relationships, women apply communal sharing but men apply authority ranking.…”
Section: Do Women Apply Communal Sharing and Equality Matching Norms mentioning
confidence: 99%
“…Recent studies have described creativity as a paradox that requires new practices and actions as well as stability, norms and routines (Fortwengel et al, ; Goncalo, Chatman, Duguid, & Kennedy, ). We shed new light on one paradox that involves balancing novelty and conformity.…”
Section: Resultsmentioning
confidence: 99%